2020
DOI: 10.1166/jctn.2020.8766
|View full text |Cite
|
Sign up to set email alerts
|

Problem Solving Skills Among Graduate Engineers: A Systematic Literature Review

Abstract: Industrial Revolution 4.0 has been one of the most popular topics discussed among engineers. In the near future the non-technical skills will be equally or more important than technical skills. Moreover, IR4.0 will incur job displacement and majority of the task will be taken over by robots and Artificial Intelligent (Tapsir, S.H. and Puteh, M., 2018. Framing Malaysian Higher Education 4.0). Therefore, priority will be given to non-technical skills which cannot be done completely by the robots and Artificial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In terms of its efficacy in helping engineers to identify and solve problems, problem handling has several advantages. According to Subramaniam et al, (2020), the ability to analyze complex problems allows engineers to deconstruct them into more manageable components. This makes it easier for them to understand the problem and to identify specific solutions.…”
Section: Mathematical Competence: Analyse Problemmentioning
confidence: 99%
“…In terms of its efficacy in helping engineers to identify and solve problems, problem handling has several advantages. According to Subramaniam et al, (2020), the ability to analyze complex problems allows engineers to deconstruct them into more manageable components. This makes it easier for them to understand the problem and to identify specific solutions.…”
Section: Mathematical Competence: Analyse Problemmentioning
confidence: 99%
“…This pedagogical approach encourages the use of convergent thinking: the use of logic to arrive at one correct solution [3]. Several studies have shown that the thinking approach used to analyze traditional problems in the engineering classroom does not provide students with the required skills to solve real-world problems [4]. In contrast, authentic, open-ended projects require divergent thinking which includes independent thinking, creativity, and innovation, all of which are rarely encouraged or practiced in classes leading to capstone design courses.…”
Section: Problem Identificationmentioning
confidence: 99%